2019
DOI: 10.19101/ijatee.2019.650042
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine performance and emission characteristic enhancement using TOPSIS

Abstract: The demand for fuel is increasing, and the availability of fossil fuel reserves is limited. The amount of concern arising from the emission problems causing the environment and ecosystem are increasing exponentially. It requires the industry to find the optimum solution. Biodiesel can be stored and used as petroleum diesel. It can be used in blended or pure forms without any modification in the engine. Use of bio-diesel has shown a remarkable reduction of toxic emissions and noise and emissions. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The technique for order preference by similarity to ideal solution (TOPSIS) method transforms the output responses of each criterion into a single objective function or a preference index in order to calculate the value of the solution that comes the closest to the ideal. Dambhare et al [24] use the TOPSIS method to determine the ideal blend ratio for a stationary variable compression ratio (VCR) diesel engine running on jatropha oil biodiesel at various loads. It was found that a 10% blend with a CR of 15 was the optimum combination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technique for order preference by similarity to ideal solution (TOPSIS) method transforms the output responses of each criterion into a single objective function or a preference index in order to calculate the value of the solution that comes the closest to the ideal. Dambhare et al [24] use the TOPSIS method to determine the ideal blend ratio for a stationary variable compression ratio (VCR) diesel engine running on jatropha oil biodiesel at various loads. It was found that a 10% blend with a CR of 15 was the optimum combination.…”
Section: Literature Reviewmentioning
confidence: 99%